How to draw manga boys in simple steps - Li, Yishan, 1981- (How to draw series., 2015)
28 different characters, poses and expressions that offer a dynamic selection of Manga-style male figures. Drawing boys is a very popular subject within the manga genre and this book is perfect for anyone seeking to learn the basics of creating these delightful characters.